The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.npp.1300487
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and a CRF1 Antagonist Block the Acquisition of Opiate Withdrawal-Induced Conditioned Place Aversion in Rats

Abstract: Conditioned place aversion in rats has face validity as a measure of the aversive stimulus effects of opiate withdrawal that reflects an important motivational component of opiate dependence. The purpose of the present study was to validate conditioned place aversion as sensitive to medications that will alleviate the aversive stimulus effects of opiate withdrawal in humans, and to extend this model to the exploration of the neuropharmacological basis of the motivational effects of opiate withdrawal. Male Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 71 publications
3
87
0
1
Order By: Relevance
“…Several studies have shown that increased CRF release contributes to the anxiety and aversive states produced by drug withdrawal (Zorrilla and Koob, 2004;Gallagher et al, 2008), and recruitment of the CRF system has been hypothesized to be involved in drug dependence (Koob, 2008). Accordingly, antagonism of CRF neurotransmission attenuated the anxiety-like and aversive effects of drug withdrawal (Stinus et al, 2005). In addition, previous findings have shown anxiolytic-like action of CRF1R antagonists (Contarino and Papaleo, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have shown that increased CRF release contributes to the anxiety and aversive states produced by drug withdrawal (Zorrilla and Koob, 2004;Gallagher et al, 2008), and recruitment of the CRF system has been hypothesized to be involved in drug dependence (Koob, 2008). Accordingly, antagonism of CRF neurotransmission attenuated the anxiety-like and aversive effects of drug withdrawal (Stinus et al, 2005). In addition, previous findings have shown anxiolytic-like action of CRF1R antagonists (Contarino and Papaleo, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Systemic administration of a CRF 1 receptor antagonist and direct intracerebral administration of a peptide CRF 1 /CRF 2 antagonist also decreased opioid withdrawal-induced place aversions (Stinus et al, 2005;Heinrichs et al, 1995). Functional noradrenergic antagonists administered directly into the BNST blocked opioid withdrawal-induced place aversion, implicating the importance of noradrenergic stimulation in the stress responses that follow acute drug withdrawal (Delfs et al, 2000).…”
Section: Withdrawal/negative Affect Stagementioning
confidence: 89%
“…Although the role of CRF in negative mood states associated with nicotine withdrawal had not been investigated, experimental evidence indicates that a hyperactivity of brain CRF systems may play a role in negative emotional states associated with withdrawal from other drugs of abuse. For example, antagonism of CRF receptors has been shown to prevent the development of opioid withdrawal-induced conditioned place aversion (Heinrichs et al, 1995;Stinus et al, 2005). It has been suggested that an increased release of CRF in extrahypothalamic brain sites mediates the negative affective state of drug withdrawal (Koob and Le Moal, 2005).…”
Section: Discussionmentioning
confidence: 99%